An Analysis of “My Mother’s Room”: An Artwork by Aidin Aghdashloo - Emami, Yassaman; Goudarzi, Mostafa (Journal of History Culture and Art Research, 2017)
Aidin Aghdashloo, an Iranian prominent artist, paints and repairs artworks as well as critiques them. His collections are such titles as “Years of Fire and Snow”, “Memories from Malek Garden”, “The Apocalyptic Calamity”, “The Riddle”, “The Angels’ Pleading”, and “The Memories of Destruction”; “My Mother’s Room” is a work from the latter made in 1981, which, thematically, is very close to the artist himself and is an indispensable part of him. This paper aims to decipher this work in order to reach its underlying levels and thus its underlying meaning. The following questions are to be answered in the paper: What was the painter’s purpose of painting his mother’s room in her absence? What is the semantic relationship between the miniature (Iranian/Persian painting) on one side and the painter’s mother and her room on the other? What are the overt and covert elements in the work that help the artist to communicate his meaning to his audience? What are the similarities between his “My Mother’s Room” and his “My Mother’s Face”? What are the similarities between the painter’s two works of his mother and mother-themed portraits by other well-known painters? With which of his other works can these two mother-themed paintings be compared?